De volta às Comunidades Eclesiais de Base – Uma alternativa para a evangelização atual - Carias, Celso Pinto (Revista Eclesiástica Brasileira, 2004)
A caminho do 11º Encontro Intereclesial de Comunidades de Base (2005), muitos agentes de pastoral procuram reencontrar o ardor missionário que levou a experiência das CEBs a ser um forte sinal de esperança para os novos tempos de nossa história. No entanto, alguns percalços ao longo da caminhada conduziram a um processo de avaliação que deve ser experimentado como benção de Deus, pois permitiu que se vislumbrassem perspectivas mais abrangentes e integradoras. É nesta linha que este artigo se coloca. Chegou a hora de retomar o caminho e relançar, de maneira renovada, esta proposta evangélica de conduzir o trabalho pastoral no interior da Igreja. Abstract: As we approach the 11th Inter-ecclesial Meeting of Basic Communities (2005), many pastoral agents have been trying to find, once again, that missionary fervour that made of the Ecclesial Communities’experience a strong symbol of hope for the new times of our history. However, some obstacles on our path led to a process of evaluation that must be considered a blessing from God, since it gave us the opportunity to glimpse at some more encompassing and integrative perspectives. The present article is part of this line of thought. The time has come for us to take that path again in order to reintroduce, in a novel form, this evangelical proposal to conduct the pastoral work within the Church.